Impact of Animal Health Interventions on Greenhouse Gas Emission and Adaptive Capacity of Extensive Livestock Systems in Ethiopia: A Narrative Review - Demis, Chekol; Dagnachew, Shimelis; Fentie, Tsegaw; Mekuriaw, Shigdaf; Van Dijk, Suzanne (International Livestock Research Institute, 2025)
Increasing concentration of greenhouse gases (GHGs), mainly of CH4, N2O and CO2, in the atmosphere is the most important cause of global warming. The agricultural sector is the dominant source of these gases in developing countries, including Ethiopia, and the livestock sub-sector accounts for 14.5% of all anthropogenic GHG and 80% of all emissions from the sector. This is mainly due to the environmental impacts of livestock diseases through increased emission of GHGs from diseased and non-productive animals to the atmosphere, which challenges the adaptive capacity of livestock keepers. Animal health interventions thus can significantly reduce emissions and enhance the adaptive capacity of livestock keepers. Despite this, little attention is given to the impact of animal health interventions on reducing GHG emissions and improvements in adaptive capacity of livestock keepers, and no previous research in Ethiopia has documented such impacts yet. With that, this narrative review is written to assess the effects of animal health interventions on GHG emissions and the adaptive capacity of livestock keepers against the negative stimuli and impacts of climate change in Ethiopia. Emissions of GHGs from livestock can be reduced through effective management of production-limiting disease, as indicated in the finding that every 1% increase in parasitic worms in sheep results in a 0.52% increase in emissions. Growing lambs infected with parasitic worms were found to have 33% higher methane emissions per kg dry matter intake than their healthy counterparts. In addition, infected lambs were also found to gain weight at only 4% of the rate of healthy lambs, resulting in a delayed time to reach slaughter weight and thus greater lifetime methane production. Strategic animal health interventions in grazing lambs shorten the time to reach market weight and reduce GHG emissions per kg of live weight gain by 10%. Healthy livestock have higher productivity and less variable production than diseased livestock, giving the farmer higher and more stable returns. They also increase the availability of foods of animal origin and hence improve the livelihood and adaptive capacity of livestock keepers. These evidences signify the “two birds in one stone” type role of animal health interventions in the sense that they can reduce GHG emissions from livestock farming and at the same time enhance the adaptive capacity of livestock keepers. Hence, it is critical to incorporate animal health interventions in future government policies and programs related to climate change and adaptive capacity.